Carrot-inspired solar thermal evaporator. Issue 47 (20th November 2019) - Long, Yaojia; Huang, Shaolong; Yi, Huan; Chen, Jiaqi; Wu, Jiahao; Liao, Qiufan; Liang, Huawei; Cui, Hongzhi; Ruan, Shuangchen; Zeng, Yu-Jia
Abstract : A carrot-inspired solar thermal evaporator exhibits a water evaporation rate of 2.04 kg m −2 h −1 and an outstanding durability and stability. Abstract : Solar steam generation appears as an emerging green strategy due to its potential applications in water desalination, power generation and chemical purification. Although a variety of efforts have been devoted to developing high-efficiency solar steam generation devices, a number of challenges remain, including the relatively low thermal efficiency, the complicated process, the high cost, and the difficulty in cycling. Herein, inspired by the natural water transportation in plants, a cheap carrot-inspired solar thermal evaporator (ethanol-treated-carrot biochar, ECB) has been reported by utilizing its inherent structure, which achieves a record high evaporation rate of 2.04 kg m −2 h −1 and an apparent energy conversion efficiency of 127.8% under one-sun illumination. The inherent structure not only enables sufficient water transportation, but also offers a high light-to-heat conversion efficiency originating from the carbonized surface. Furthermore, the excellent durability and environmental stability of the biochar allow for convenient recycling programs and practical applications.